Mining claim No 17 Eldorado Creek looking up French Gulch, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (Hegg & Company, 1898)
Caption on image: "No 17 Eldorado Looking up French Gulch/Hegg & Co., Dawson, Y.T." No. 53 appears in lower left corner. Klondike Gold Rush.